Synthesis, characterization and spectroscopic properties of new fluorescent 7,8-dihexyloxy-3-(4-oxyphenyl)coumarin substituted phthalocyanines - (:unkn) unknown (WORLD SCI PUBL CO INC, 2009)
The synthesis of metal-free and metallophthalocyanines (M = Zn, Co) obtained from 7,8-dihexyloxy-3-[p-(3',4'-dicyanophenoxy)phenyl] coumarin are described. The newly prepared compounds have been characterized by elemental analysis, IR, NMR, mass and UV-vis spectral data. Their electronic absorption and fluorescence spectral properties are reported. Cyclic voltammetry of the compounds have also been studied. In situ spectroelectrochemistry of the Co(II) complex in THF and DCM is included to identify the difference in its redox behavior, as compared with other complexes.
Keywords: coumarin; fluorescence; aggregation; cyclic voltammetry; spectroelectrochemistry; CHROMENONE-CROWN ETHERS; ELECTROCHEMICAL CHARACTERIZATION; PHOTOCHEMICAL FORMATION; ZINC PHTHALOCYANINE; METAL-FREE; COMPLEXES; ZN(II); COBALT; COUMARINS; MANGANESE